The association between selenium and lipid levels: A longitudinal study in rural elderly Chinese. Issue 1 (January 2015) - Chen, Chen; Jin, Yinlong; Unverzagt, Frederick W.; Cheng, Yibin; Hake, Ann M.; Liang, Chaoke; Ma, Feng; Su, Liqin; Liu, Jingyi; Bian, Jianchao; Li, Ping; Gao, Sujuan
Highlights In 7-year follow up of an elderly Chinese cohort including participants from selenium-deplete areas, we found that subjects with the higher selenium levels had greater decrease in total cholesterol and greater increase in HDL from baseline to follow-up examination compared to those with lowest selenium levels, suggested that adequate dietary selenium intake as a potential prevention strategy for lowering lipid levels in selenium deplete populations. In prospective analysis, we found that participants with the higher selenium levels had greater decrease in total cholesterol and greater increase in HDL from baseline to follow-up examination compared to those with lowest selenium levels, which suggested that adequate dietary selenium intake as a potential prevention strategy for lowering lipid levels in selenium deplete populations.